CHEMICAL CONTROL AND MORPHOANATOMICAL ANALYSIS OF LEAVES OF DIFFERENT POPULATIONS OF SOURGRASS - Gomes, L. J. P. [UNESP]; Santos, J. [UNESP]; Gasparino, E. C. [UNESP]; Correia, N. M. (Univ Federal Vicosa, 2017)
Digitaria insularis has been selected by frequent glyphosate applications both in no-till areas and in fruit orchards. The objective of this paper was to evaluate control efficacy of D. insularis populations by glyphosate, alone and mixed with quizalofop-p-tefuryl, as well as classify them for herbicide sensitivity as susceptible, moderately susceptible and tolerant. This study also aimed to evaluate the relations between herbicide sensitivity and morphoanatomic features of leaf tissues. For chemical control, the experiment was conducted in a completely randomized design, with a 12 x 4 factorial arrangement with four replications. Twelve populations of D. insularis were treated with glyphosate alone at two concentrations (1.44 and 2.16 kg a. e. ha(-1)) and with the mixture of glyphosate (2.16 kg a. e. ha(-1)) and quizalofop-p-tefuryl (0.12 kg a. i. ha(-1)). One treatment without herbicide application was maintained for each plant population. Evaluations about the morphoanatomic features and wax content of leaves from the twelve plant populations were made under laboratory conditions. Populations 3, 5, 6 and 8 were considered to be susceptible; 9, 10 and 12 were considered as moderately susceptible; 1, 2, 4, 7 and 11 were considered tolerant to glyphosate. However, populations within each group (susceptible, moderately susceptible and tolerant) did not have similar characteristics that justify their response to glyphosate. Differences relative to herbicide translocation and/or plant physiology could account for the chemical control results for these populations.
Keywords: Digitaria insularis; glyphosate; tolerance; genetic variability